2013
DOI: 10.7314/apjcp.2013.14.3.1937
|View full text |Cite
|
Sign up to set email alerts
|

Different Association of Manganese Superoxide Dismutase Gene Polymorphisms with Risk of Prostate, Esophageal, and Lung Cancers: Evidence from a Meta-analysis of 20,025 Subjects

Abstract: Altered expression or function of manganese superoxide dismutase (MnSOD) has been shown to be associated with cancer risk but assessment of gene polymorphisms has resulted in inconclusive data. Here a search of published data was made and 22 studies were recruited, covering 20,025 case and control subjects, for metaanalyses of the association of MnSOD polymorphisms with the risk of prostate, esophageal, and lung cancers. The data on 12 studies of prostate cancer (including 4,182 cases and 6,885 controls) showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
(43 reference statements)
1
10
1
Order By: Relevance
“…(46) Of these, SOD2 has been investigated the most with regards to prostate cancer, and several,(47-49) but not all(50) meta-analyses have reported significant associations between genetic variants in SOD2 and risk of prostate cancer, particularly for more aggressive disease. We and others have previously reported on potential interaction effects between SNPS in SOD1 , SOD2, selenoprotein or selenobinding proteins, and selenium status, and risk of aggressive prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…(46) Of these, SOD2 has been investigated the most with regards to prostate cancer, and several,(47-49) but not all(50) meta-analyses have reported significant associations between genetic variants in SOD2 and risk of prostate cancer, particularly for more aggressive disease. We and others have previously reported on potential interaction effects between SNPS in SOD1 , SOD2, selenoprotein or selenobinding proteins, and selenium status, and risk of aggressive prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results have remained inconsistent or even contradictory. In addition, lack of research using different stratified analyses has prevented a comprehensive understanding of the relationship between MnSOD Val16Ala polymorphism and the risk of PCa in some recent meta-analyses (31)(32)(33)(34). Therefore, to clarify the nature of the association, a meta-analysis was conducted including all eligible articles to gather the statistical evidence.…”
mentioning
confidence: 99%
“…For 51 SNPs identified by meta‐analysis, 38 SNPs had statistically significant association with EC or ESCC susceptibility . Meta‐analysis results showed that there were 27 SNPs associated with increased EC or ESCC risk, whereas 11 SNPs decreased the risk of EC or ESCC risk.…”
Section: Resultsmentioning
confidence: 94%